2017
DOI: 10.3390/rel8080154
|View full text |Cite
|
Sign up to set email alerts
|

Job Status of Women Head Clergy: Findings from the National Congregations Study, 1998, 2006, and 2012

Abstract: This paper investigates occupational gender inequality among head clergy in U.S. religious congregations. Prior research emphasized the stratification of the clergy occupational structure and the under-representation of women in head clergy positions. This paper focuses on women who are leading congregations. Data are from the National Congregations Study (1998, 2006, and 2012). I review the representation of women among head clergy, investigate the differences in congregational characteristics between those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 37 publications
(59 reference statements)
0
9
0
3
Order By: Relevance
“…This often creates a culture that limits female pastors' advancement, especially in the church (Chifungo, 2015). In the United States, a study spanning the period 1998-2012 has observed a lack of acceptance of female pastors in the ministry, especially in large congregations and non-white sample communities (Hoegeman, 2017).…”
Section: Empirical Literaturementioning
confidence: 99%
“…This often creates a culture that limits female pastors' advancement, especially in the church (Chifungo, 2015). In the United States, a study spanning the period 1998-2012 has observed a lack of acceptance of female pastors in the ministry, especially in large congregations and non-white sample communities (Hoegeman, 2017).…”
Section: Empirical Literaturementioning
confidence: 99%
“…Az ezzel foglalkozó elemzések a lelkésznők helyzetének vizsgálatát így gyakran a vallásszociológia és a munka-vagy foglalkozásszociológia közös területeként fogják fel (De Gasquet 2010, Offenberger 2013, Nesbitt 2013. A legszembetűnőbb analógia a világi foglalkozásokkal a vertikális szegregáció tekintetében figyelhető meg, azaz bár a nők jelenléte az egyházban érzékelhetően növekszik, a lelkésznők nehezebben jutnak megfelelő munkához vagy alacsonyabb státuszú munkát kapnak, és az egyházi hierarchiában 11 felfelé haladva egyre kevesebb nőt találunk (Finlay 1996, Charlton 1997, Sullins 2000, Chang 2005, Hoegeman 2017). Ennek leírására -világi foglalkozások esetében használt "üvegplafon" mintájára -az Egyesült Államokban a kilencvenes évek óta elterjedt a "stained glass ceiling" kifejezés (Purvis 1995, Sullins 2000.…”
Section: Nők a Kereszténységben Nők Az Egyházbanunclassified
“…Paul Sullins (2000) azonban az amerikai episzkopális és presbiteriánus egyházakban vizsgálódva nemcsak azt találta, hogy a női lelkészek változatlanul fölülreprezentáltak az alárendelt és az alacsonyabb státuszú pozíciókban, hanem azt is, hogy ez az egyenlőtlenség figyelemreméltóan állandó: nem csökken sem időben, sem a lelkészi karrier során. Bár a lelkésznők folyamatosan növekvő arányával természetesen mindenütt egyre többen törik át az "ólomüveg plafont", egy 2012-ig terjedő adatokat elemző kutatás úgy találta, hogy az Egyesült Államokban változatlanul kisebb valószínűséggel kerülnek önálló gyülekezetvezető lelkészi pozícióba, mint a férfiak (Hoegeman 2017). Mindazonáltal ugyanez a kutatás megállapítja, hogy -szemben a korábbi eredményekkel (Chang 2005) -az önálló gyülekezeti lelkészek esetében már nincs jelentős különbség nők és férfiak között annak a valószínűségében, hogy vezető lelkészek (tehát más, beosztott lelkészeket is felügyelő "senior pastor"-ok) legyenek, vagyis a viszonylag nehezebben áttörhető határvonal az önálló gyülekezeti lelkész pozíciójánál húzódik (Hoegeman 2017).…”
Section: Nők a Kereszténységben Nők Az Egyházbanunclassified
See 1 more Smart Citation
“…The women's movement of the 1970s and increased acceptance and scholarly support of the egalitarian viewpoint has affected the roles of women inside and outside the church (Coder & Spiller, 2013). However, the church lags in hiring women for upper levels of pastoral leadership due to a variety of current leadership structures and church constituent beliefs and preferences (Hoegeman, 2017). Beliefs include the complementarian and egalitarian gender role perspectives held by individual denominations and churches (Scott, 2002).…”
Section: Cultural Contextmentioning
confidence: 99%